Pengaruh Penggunaan Filter DC pada Penyerarah Gelombang Penuh Tiga Fasa - Amirullah, Amirullah (Rekayasa, 2008)
This paper presents effect of use defilters on three phases offull wave rectifier. Three phases offull wave rectifier are commonly used inhighpower application. It can be operated with or without a transformer and give six pulse ripples on the output voltage. Wehave notice that the output of the rectifier contains harmonic. Filter can be used to smooth out the de output voltage and current of the rectifier and these are known as defilters. Thedefilters are usually of L, C, and LC type. By inserting the defilter on the output of three phases full wave rectifier, can reduce ripple de output voltage and current of the rectifier. As result, depend onwithoutfilter, L typefilter, and C typefilter, LC typefilter give the bestperformance because it can smooth out the de output voltage and current of the rectifier and minimize ripple of wave or ripplefactor (RF) almost as zero valued.